Redescription of immature stages of central European fireflies, Part 1: Lampyris noctiluca (Linnaeus, 1758) larva, pupa and notes on its biology (Coleoptera: Lampyridae: Lampyrinae) - Novák, Martin (Zootaxa, 2017)
The mature larva of Lampyris noctiluca (Linnaeus, 1758) is redescribed and illustrated in detail, including scanning electron microscope images. Male and female pupae are briefly described, including notes on behaviour as well as light production of the immature stages. Observed structures, life cycle and behaviour of larvae and pupae are discussed.
Keywords: larva; Evropa; Coleoptera, Lampyris noctiluca, larva, pupa, morphology, ecology; kukla; mužské pohlaví; Larva; světluškovití; ženské pohlaví; zvířata; Female; Pupa; Europe; Fireflies; Male; Animals